2015
DOI: 10.1039/c5dt02032h
|View full text |Cite
|
Sign up to set email alerts
|

A new cube-based dodecanuclear cobalt(ii) cluster with azide and tetrazolate ligands exhibiting ferromagnetic ordering

Abstract: A new cubane-based Co(ii) compound, [Co(12)(5-PT)(6)(CO(3))(N(3))2(O)(4)(CH(3)O)(6)(H(2)O)(18)] (1) (5-HPT = 5-phenyl-1H-tetrazole), was synthesized by reaction of 5-HPT, CoCl(2)·6H(2)O and NaN(3) in a methanol solution. In 1, a Co(12) cluster based on three identical Co(4)O(2)(ON)(2) cubane units bridged by a μ(6)-carbonate ligand is linked by π-π stacking interactions between phenylene groups, forming a 3D supramolecular structure. Magnetic investigations indicate that compound 1 exhibits long-range ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…17,18 In addition, a carbonate anion is also a good bridge due to its various bridging modes, such as μ 2 -CO 3 2− , 19,20 μ 3 -CO 3 2− , 21,22 μ 4 -CO 3 2− , 23,24 and μ 6 -CO 3 2− . [25][26][27] Furthermore, we found that calix [8]…”
Section: Introductionmentioning
confidence: 74%
“…17,18 In addition, a carbonate anion is also a good bridge due to its various bridging modes, such as μ 2 -CO 3 2− , 19,20 μ 3 -CO 3 2− , 21,22 μ 4 -CO 3 2− , 23,24 and μ 6 -CO 3 2− . [25][26][27] Furthermore, we found that calix [8]…”
Section: Introductionmentioning
confidence: 74%
“…However, it is difficult to theoretically analyze the magnetic susceptibility data of Co­(II) complexes, , because there are strong spin–orbit coupling and highly magnetic anisotropy in Co­(II) ion. Vilminot et al point out, Co­(II) is a Kramer’s ion with a considerable spin–orbit coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The syn−syn η 1 η 1 -μ 2 -carboxylic groups can transmit antiferromagnetic interaction, whereas monodentate-bridging η 0 η 2 -μ 2 -carboxylic group can mediate ferromagnetic interaction. 30 However, it is difficult to theoretically analyze the magnetic susceptibility data of Co(II) complexes, 57,58 because there are strong spin−orbit coupling and highly magnetic anisotropy in Co(II) ion. Vilminot et al point out, 51 Co(II) is a Kramer's ion with a considerable spin−orbit coupling.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The Co II material has a room temperature χT of 12.0 cm 3 K/mol for two formula units. Although the spin‐only χT value of four non‐interacting S = 3/2 ions in two formula units is 7.50 cm 3 K/mol, a significantly elevated χT observed for Co II ions is a well‐documented phenomenon arising from unquenched spin‐orbit coupling . Upon cooling below 300 K, χT decreases continuously.…”
Section: Resultsmentioning
confidence: 99%